Laporan Sumber Modal dan Penggunaan Modal Kerja Pada Perusahaan Handjaya Mandala Sampoerna Tbk Di Bursa Efek Indonesia (BEI) - Diana Fransiska; M. Aryo Arifin; Andri Eko Putra (Jurnal Media Akuntansi (Mediasi), 2021)
ABSTRACT The purpose of this study was to find out the report on sources of capital and the use of working capital at the Handjaya Mandala Sampoerna Tbk Company on the Indonesia Stock Exchange. PT Handjaya Mandala Sampoerna is one of the leading cigarette industries in the country which has been established since 1913 in the city of Surabaya, until now Handjaya Mandala Sampoerna has been widely known both domestically and abroad as a producer of high quality kretek cigarettes. Reports on sources of capital and use of working capital are used to find out the results of financial activities in the company in a certain period and to see the causes of changes in working capital and to find out reports on sources of capital and use of working capital. The research method used by the author is descriptive and quantitative methods. The data used is secondary data in the form of financial statements. The data collection technique used is the documentation technique. The results of this study indicate that the Handjaya Mandala Sampoerna Tbk Company on the Indonesia Stock Exchange in compiling the comparative balance sheet in 2016-2017 and 2018 the company always experiences an increase in working capital every year. This is due to an increase in assets that is greater than the increase in total current liabilities. And the report on changes in working capital has a fairly good working capital management because in 2016-2017 it experienced an increase of Rp. 632,786 and from 2017-2018 it can be seen that the management of working capital continues to result in an increase in working capital. While the results of the report on sources of capital and the use of working capital of Pt Handjaya Mandala Sampoerna Tbk have a good source of working capital because in 2016-2017 and 2018 the source of working capital is greater than the use of working capital. Keyword: sources of capital, use of working capital.  ABSTRAK Tujuan penelitian ini untuk mengetahui Laporan Sumber Modal Dan Penggunaan Modal Kerja Pada Perusahaan Handjaya Mandala Sampoerna Tbk Di Bursa Efek Indonesia. PT Handjaya Mandala Sampoerna merupakan salah satu industri rokok termuka di tanah air yang telah berdiri sejak tahun 1913 di kota Surabaya, hingga kini Handjaya Mandala Sampoerna sudah terkenal luas baik di dalam negeri maupun mancanegara sebagai penghasil rokok kretek berkualitas tinggi. Laporan sumber modal dan penggunaan modal kerja digunakan untuk mengetahui hasil-hasil aktivitas keuangan pada perusahaan dalam suatu periode tertentu dan utuk melihat penyebab-penyebab terjadinya perubahan modal kerja serta untuk mengetahui  laporan sumber modal dan penggunaan modal kerja. Metode penelitian yang digunakan penulis adalah motode Deskriftif dan Kuantitatif. Data yang digunakan yaitu data sekunder berupa laporan keuangan. Teknik pengumpulan data yang digunakan adalah teknik dokumentasi. Hasil penelitian ini menunjukan bahwa Perusahaan Handjaya Mandala Sampoerna Tbk Dibursa Efek Indonesia dalam menyusun neraca perbandingan pada tahun 2016-2017 dan 2018 perusahaan setiap tahunnya selalu mengalami peningkatan modal kerja. Hal ini disebabkan peningkatan aktiva yang lebih besar dibandingkan dengan peningkatan total kewajiban lancarnya. Dan laporan perubahan modal kerja memiliki pengelolaan modal kerja yang cukup baik karena ditahun 2016-2017 mengalami prningkatan Rp 632.786 dan dari tahun 2017-2018 terlihat pengelolaan modal kerjanya yang terus menghasilkan peningkatan modal kerja. Sedangkan hasil laporan sumber modal dan penggunaan modal kerja Pt Handjaya Mandala Sampoerna Tbk ini memiliki sumber modal kerja yang baik karena ditahun 2016-2017 dan 2018 sumber modal kerjanya lebih besar dari pada penggunaan modal kerja. Kata Kunci : Sumber Modal, Penggunaan Modal Kerja